Prevalence and correlates of low back pain among undergraduate medical students in Serbia, a cross-sectional study - Ilic, Irena (PeerJ, 2021)
BACKGROUND: Low back pain (LBP) is a serious health problem among medical students. We aimed to investigate the prevalence and associated factors for LBP among Serbian medical students. METHODS: A cross-sectional study was performed among medical students at one University in Serbia. Data was collected by a self-reported questionnaire. Logistic regression was used to determine the factors associated with LBP; results from the analyses were expressed as odds ratios (OR) with 95% confidence intervals (CI). RESULTS: The study sample comprised 499 medical students, giving a response rate of 92.9%. The mean age of the participants was 22.0 ± 2.2 years (range 18–34). Overall, 20.8% (104/499) of medical students had LBP at the time of study. Cigarette smoking (OR = 2.5, 95% CI [1.5–4.2], p = 0.001), stress during classes (OR = 1.8, 95% CI [1.1–3.0], p = 0.039), incorrect sleeping position (OR = 1.9, 95% CI [1.2–3.1], p = 0.006) and family history of LBP (OR = 1.6, 95% CI [1.1–2.7], p = 0.047) were independently associated with high prevalence of LBP at the time of the study. CONCLUSIONS: LBP is a highly prevalent health problem in medical students in Serbia. The association between LBP and cigarette smoking, stress during classes, incorrect sleeping position and LBP in family history has been observed in medical students.